Biophysics of the elite endurance swimmer: A case study during aerobic capacity evaluation using different methods - Pelarigo, J. G.; Denadai, B. S.; Ribeiro, J.; Fernandes, R. J.; Greco, C. C.; Vilas-Boas, J. P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Introduction: In swimming research, the characterisation of various parameters are generally accomplished by its reduction to the mean and standard deviation. This procedure allows analyzing the tendencies and/or the variability of a group. However, in doing so, individual characteristics of an elite swimmer may be hidden by the group tendency. Thereby, the purpose of this case study was to analyze one elite endurance swimmer comparing biomechanical and physiological parameters among the main methods used for aerobic capacity evaluation. Methods: The elite female endurance swimmer (18 yrs, 1.64 m, 56 kg, 91.% 400m freestyle WR) performed in different days: 1) an intermittent incremental protocol until voluntary exhaustion to determine the velocity (v) associated at the individual lactate threshold (I LT), the ventilatory threshold (VT), the heart rate threshold (HRT), the lactate threshold of fixed 3.5mmoi.L-1 (L T3.5), maximal oxygen uptake (VOzmax), and minimal v that elicits V02max (vV02maxl; 2) three 30min sub-maximal continuous tests to determine the v and oxygen uptake (VQ 2) kinetics associated at the maximal lactate steady state test (100%MLSS), above (102.5%MLSS) and below (97.5%MLSS) this intensity. Blood lactate collection (Bla), v, ventilatory, energetic and biomechanical parameters were controlled in all tests. Results: The results showed a close relationship among the 100%MLSS, ILT and VT regarding the v, ventilatory, energetic and biomechanical parameters. Meanwhile, LT3.5 and vV02 max presented higher values in all these parameters. Key points were noticed: 1) the oxygen uptake efficiency values (QUE) presented an uncommon stability and linear relationship with the v until VQ 2max• while the remaining swimmers showed decreased values of QUE, largely determined by metabolic acidosis and pulmonary dead space (Sun, Hansen & Stringer 2012). Thus, this maintenance of QUE may be explained by the low Bla observed in swimmer's vVQ 2 max (4.4mmolr\ 2) V02 slow component was not observed in both intensities of 100%MLSS and 102.5%MLSS; 3) the 100%MLSS v was very high (92.6% vVQ2 maxl implying low \ioz values (77.5% VOzmaxl· Conclusion: Thereby, the analysis of individual characteristics of specific athletes, particularly elite swimmers, rather than rely upon mean sample values, may be decisive to understand the specific intervention required and to improve performance.